Development finance : debates, dogmas and new directions - Spratt, Stephen (New York, NY : Routledge, 2008)
This book examines the subject of Development Finance, or more specifically how financial systems can help or hinder the process of human development. As an expert in this field, Stephen Spratt reviews the components of the domestic and international financial systems, and considers reform options objectively against the central goal of human development. The result is a combination of orthodox and more innovative approaches, which provides a thorough grounding in development finance theory and practice in the 21st century.
Includes bibliographical references and index.
rpm 02/05/13
Loans
Keywords: Finance - developing countries; Economic development - finance; International finance; Development finance